2016
DOI: 10.3389/fnbeh.2016.00104
|View full text |Cite
|
Sign up to set email alerts
|

DYRK1A, a Dosage-Sensitive Gene Involved in Neurodevelopmental Disorders, Is a Target for Drug Development in Down Syndrome

Abstract: Down syndrome (DS) is one of the leading causes of intellectual disability, and patients with DS face various health issues, including learning and memory deficits, congenital heart disease, Alzheimer’s disease (AD), leukemia, and cancer, leading to huge medical and social costs. Remarkable advances on DS research have been made in improving cognitive function in mouse models for future therapeutic approaches in patients. Among the different approaches, DYRK1A inhibitors have emerged as promising therapeutics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
152
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 230 publications
(232 reference statements)
8
152
0
Order By: Relevance
“…Furthermore, Dyrk1a appears to have a crucial role during central nervous system development (CNS), via its regulation of multiple targets in both the nucleus and the cytoplasm via phosphorylation [extensively reviewed in (Becker et al. ; Duchon and Herault )]. Normalization of Dyrk1a copy number in otherwise trisomic mouse models has resulted in some improvements in cognitive and behavioral phenotypes (Garcia‐Cerro et al.…”
Section: The Role Of Ds Mouse Models In Finding Therapiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, Dyrk1a appears to have a crucial role during central nervous system development (CNS), via its regulation of multiple targets in both the nucleus and the cytoplasm via phosphorylation [extensively reviewed in (Becker et al. ; Duchon and Herault )]. Normalization of Dyrk1a copy number in otherwise trisomic mouse models has resulted in some improvements in cognitive and behavioral phenotypes (Garcia‐Cerro et al.…”
Section: The Role Of Ds Mouse Models In Finding Therapiesmentioning
confidence: 99%
“…Several recent reviews have discussed in detail the numerous targets of Dyrk1a , and have suggested how molecular mechanisms altered by excessive Dyrk1a could affect cognitive and behavioral processes (Wegiel et al. ; Park and Chung ; Duchon and Herault ; Antonarakis ). In addition, several reports have described potential Dyrk1a inhibitors and their possible use for correcting DS‐related deficits (de la Torre and Dierssen ; Becker et al.…”
Section: The Role Of Ds Mouse Models In Finding Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In mouse, DYRK1A is essential for embryonic development, especially in the nervous systems, and unbalanced gene dosage causes developmental delay and abnormal brain morphology [68][69][70][71][72][73][74][75]. In neuronal progenitor cells, overexpression of DYRK1A bring to the attenuation of cell proliferation that promotes the switch to a quiescent state or differentiation.…”
Section: Dual Specificity Tyrosine Phosphorylation-regulated Kinases mentioning
confidence: 99%